A molecular systematic analysis of the Neotropical banner winged damselflies (Polythoridae: Odonata) (2018)
The Neotropics are a hotspot of global diversity for many groups of organisms, including the dragonflies and damselflies (Insecta: Odonata). While the number of biodiversity surveys and new species descriptions for Neotropical odonates is increasing, diversity in this region is still under-explored, and very few studies have looked at the genetic and morphological diversity among (and within) species. Here, we present an overview of the evolutionary history of the Neotropical damselfly family Polythoridae. The family comprises 57 species across seven genera: Chalcopteryx Selys, Chalcothore De Marmels, Cora Selys, Euthore Selys, Miocora Calvert, Polythore Calvert and Stenocora Kennedy. Using a multi-locus approach, mitochondrial (COI, ND1, 16S) and nuclear (18S, 28S, EF1-alpha) genes were concatenated to estimate phylogenetic relationships. Our results support five monophyletic clades, which were not always congruent with the genera previously considered to be monophyletic. Only Polythore was recovered as monophyletic, and within it there was geographical structure. We propose the following new genus-level classification: Chalcothore, Chalcopteryx, Cora s.s., Cora s.l., Miocora, Euthore s.l and Polythore. In addition, we proposed the following new combinations: Miocora aurea comb.n., Miocora chirripa comb.n., Euthore confusa comb.n., Euthore klenei comb.n., and Euthore terminalis comb.n., based on our phylogenetic analyses, our evaluation of morphological characters and their geographical distribution: these data each support the monophyletic entities we recover here. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:E9E10CD8-6A04-4F2E-A632-1B998BAFB193. © 2017 The Royal Entomological Society